THE MODERATING ROLE OF LEADERSHIP FOR FRAUD PREVENTION EFFORTS IN PUBLIC SECTOR - Bisma Akbar Anggara Surya; Amrie Firmansyah (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2024)
This Fraud continues to be rampant in Indonesia. It follows an ACFE poll performed in 2019. This survey uncovers at least 239 fraud incidents in Indonesia, resulting in a total loss of IDR. 873,430,000,000.00. However, there is a belief that there is no fraud prevention in Indonesia. Indonesia has various Ministries/Institutions in charge of combatting fraud, including the Financial and Development Supervisory Agency. As one of the Ministries/Institutions that has the task of preventing fraud, fraud prevention at the Financial and Development Supervisory Agency must be able to run well. All leaders of Government Agencies are required to uphold integrity and ethical values, commit to competence, and create conducive leadership so that the variables integrity, competence, and internal control system are determined as independent variables that are tested for their influence on fraud prevention efforts with leadership as a moderating variable. The research results show that integrity and internal control systems positively affect fraud prevention efforts, while competency has no effect. Meanwhile, the leadership fails to moderate all variable relationships. Thus, in fraud prevention efforts, the most influential variables in this research are integrity and internal control systems.